Metodological basis of the Fridrich Frobel’s pedagogical system - Анісімова, О. Е. (Pedagogy of Higher and Secondary Education, 2013)
Anisimova E. E. Metodological basis of the Fridrich Frobel’s pedagogical system. The article represents the methodological basis of the pedagogical system of the prominent German pedagogue Friedrich Frobel. The author divulges the main aspects of Frobel’s ideas about the theory and practice of bringing up a child of preschool age.